Relatives' experiences of visiting restrictions during the COVID-19 pandemic's first wave: a PREMs study in Valais Hospital, Switzerland - N. Tacchini-Jacquier; S. Monnay; E. Bonvin; J. Dubuis; H. Verloo (BMC, 2023)
Abstract Background During the COVID-19 pandemic, most countries introduced temporary visiting restrictions on the relatives of acute care hospital patients, whether or not they were infected with SARS-CoV-2. This affected relatives' psychological and emotional states and how closely they could be involved in their loved one's hospitalization. Study aims Investigate relatives' experiences of visiting restrictions during the COVID-19 pandemic's first wave and the support offered by Valais Hospital's healthcare staff. Methods Relatives and patients who had been discharged between February 28 and May 13, 2020, were asked to complete a patient-reported experience measures (PREMs) questionnaire, whether or not they had been infected by SARS-CoV-2. Relatives were asked about how visiting restrictions had affected them, their perceptions of the severity of the COVID-19 pandemic, the quality of communication concerning their loved ones' health status during their hospitalization, and the information received from healthcare staff. Descriptive and inferential statistics were computed. Results Of 866 PREMs questionnaires returned, 818 were analyzable, and 543 relatives had experienced visiting restrictions to their loved ones: 92 relatives (87%) of COVID-19 patients and 451 relatives (66%) of non-infected patients, with heterogenous effects on their psychological and affective status. Overall, whether or not relatives were subjected to visiting restrictions, they perceived themselves to be well treated, well informed, and that communication with hospital healthcare staff was satisfactory. However, relatives subjected to visiting restrictions reported significantly lower scores on the quality of communication than other relatives. The relatives of patients in gynecology/obstetrics and internal medicine wards were significantly more affected by visiting restrictions than were the relatives of patients in other wards. Numerous relatives subjected to visiting restrictions reported regular communication with their loved ones or with healthcare staff, at least once a day (n = 179), either via videoconferences using FaceTime®, WhatsApp®, Zoom®, or Skype® or via mobile phone text messages. Conclusion Visiting restrictions affected relatives differently depending on the wards their loved ones were hospitalized. Healthcare institutions should investigate the utility of visiting restrictions on patients, how they affect relatives, and how to improve personalized patient-relative communications. Future research should attempt to develop reliable, validated measurement instruments of relatives' experiences of acute-care visiting restrictions during pandemics.